HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN PENDERITA TB PARU DENGAN PERILAKU PEMBUANGAN DAHAK DI PUSKESMAS REWARANGGA KECAMATAN ENDE TIMUR KABUPATEN ENDE - MARIETA KRISTINA S. BAI (JURNAL INFO KESEHATAN, 2014)
TB disease is one public health problem. According to WHO (2003), approximately eight million people with tuberculosis attacked three million deaths per year. An estimated 95% of TB patients in developing countries and represents 25% of the deaths that could have held the disease prevention. One cause is the behavior of TB disease transmission. The purpose of the study was to analyze the relationship of education and knowledge level of patients with pulmonary tuberculosis in sputum disposal behavioral health center Rewarangga Eastern District of Ende. The method used is an analytical study with cross sectional approach. Data were collected using a questionnaire and the results of recording data at the health center. This study was conducted on 20 respondents from a population of patients undergoing treatment. Respondents who had elementary as much as 15%, 40% junior high, high school 40%, 5% Bachelor, knowledgeable and everything nice. 100% of respondents were knowledgeable good, 55% of respondents dispose of sputum expectoration in landfills, and 45% of respondents dispose of sputum is not in place. There is no relationship between education and behavior sputum disposal and there is a relationship between knowledge and behavior of sputum disposal. It is expected that TB sufferers behave so as not to infect the illness to others.